Benefits Of Organizational Commitment And Job Satisfaction In Solving Employee Performance Problems In Micro And Medium Enterprises In Serang Banten - Hamdan, Hamdan (International Journal of Educational Research & Social Sciences, 2022)
This study aims to determine the effect of Organizational Commitment and Job Satisfaction on Employee Performance in Micro and Medium Enterprises in Serang Regency, Banten. The method used is quantitative. The type of data used in this study is in the form of secondary data based on the results of the questionnaire. In this study the authors used two independent variables consisting of (Organizational Commitment and Job Satisfaction) or called the independent variable and one dependent variable (Employee Performance) which is known as the dependent variable. The population in this study were employees of the Micro and Medium Enterprises in Serang Banten Regency as many as 42 employees. Data were analyzed using multiple linear regression models and using SPSS version 25. Based on the results of the study, it can be concluded that: 1). There is no positive and significant effect between Organizational Commitment on Employee Performance. 2). There is a positive and significant influence between job satisfaction on employee performance. 3). Simultaneously there is a positive and significant influence between Organizational Commitment and Job Satisfaction on Employee Performance.